A study on the bacteriological profile of urinary tract infection in adults and their antibiotic sensitivity pattern in a tertiary care hospital in central Kerala, India - A. T., Jubina Bency; R., Priyanka; Jose, Ponnu (International Journal of Research in Medical Sciences, 2017)
Background: Urinary tract infection is one of the most common bacterial infections in humans and a major cause of morbidity. The etiology of UTI and the antibiotic sensitivity pattern varies with the widespread availability of antimicrobial agents; UTI has become difficult to treat because of appearance of pathogens with increasing resistance to antimicrobial agents. Methods: A descriptive study done during January-June 2013. All positive urine culture and sensitivity reports of males and females aged 20-70years were included. A total of 373 positive urine culture cases were taken from the culture and sensitivity register from Microbiology department and details were entered using a questionnaire. Results: Out of 373 adults, males were 137 (36.7%) and females were 236 (63.3%). E. coli (74.3 %) was the most common organism, followed by Klebsiella (15.8%), Enterococcus, Pseudomonas and Staphylococcus. The incidence of UTI was more in patients in the age group of 60-70years. E. coli and Klebsiella were sensitive to Amikacin (97.1%), Nitrofurantoin (90.7%), Gentamycin and Imipenem. Both organisms were resistant to Ampicillin (>90%). Conclusions: In this study, females were mostly affected and the most common organisms were E.Coli and Klebsiella. These organisms were most sensitive to Amikacin, Nitrofurantoin and resistant predominantly to Ampicillin. The sensitivity and resistance pattern of uropathogens to common antimicrobial agents must be taken into account when selecting treatment plans for UTI.